CARBON ISOTOPIC FRACTIONATION BY ARCHAEANS AND OTHER THERMOPHILIC PROKARYOTES - House C.H.; Schopf J.W.; Stetter K.O. (My University, 2003)
This study of carbon isotopic fractionation in a wide array of 21 phylogenetically diverse microbial species provides an opportunity to correlate carbon isotopic fractionations with a biochemical pathway. These carbon isotopic fractionation experiments included two members of the Aquificales and two members of the Thermoproteales using the reductive TCA cycle, three members of the Sulfolobales using the 3-hydroxypropionate cycle, as well as three Archaeoglobales and seven methanogens using the acetyl-CoA pathway. In these experiments, microorganisms using the reductive tricarboxylic acid cycle (with # values between 2.0 and 5.5%%) and the 3-hydroxypropionate cycle (with # values between 0.2 and 3.6%%) demonstrated significantly less carbon isotopic fractionation than methanogens using the acetyl-CoA pathway. The results reported here for the acetyl-CoA pathway-utilizing microbes, however, vary over a remarkably wide range with # values of 2.7 to 8.0%% for the Archaeoglobales and # values of 4.8 to 26.7%% for the methanogens. The magnitude of carbon isotopic fractionation observed in species of Methanococcus were related to the particular growth status that had been attained by the various cultures, with increasing isotopic fractionation as growth proceeded.